Modulation of receptor binding to collagen by glycosylated 5‐hydroxylysine: Chemical biology approaches made feasible by Carpino's Fmoc group. Issue 4 (19th March 2020) - Cudic, Maré; Fields, Gregg B.
Abstract: The creation of the 9‐fluorenylmethoxycarbonyl (Fmoc) group by the Carpino laboratory facilitated the synthesis of peptides containing acid‐sensitive groups, such as O ‐linked glycosides. To fully investigative collagen biochemistry, one needs to assemble peptides that possess glycosylated 5‐hydroxylysine (Hyl). A convenient method for the synthesis of Fmoc‐Hyl(ε‐ tert ‐butyloxycarbonyl (Boc), O ‐ tert ‐butyldimethylsilyl [TBDMS]) and efficient methods for the synthesis of Fmoc‐Hyl[ε‐Boc, O ‐(2, 3, 4, 6‐tetra‐ O ‐acetyl‐β‐D‐galactopyranosyl)] have been developed. Glycosylated Fmoc‐Hyl derivatives were used to construct a series of types I‐IV collagen‐model triple‐helical peptides (THPs) that incorporated known or proposed receptor binding sites. Glycosylation of Hyl was found to strongly down‐regulate the binding of CD44 and the α3β1 integrin to collagen, while the impact on α2β1 integrin binding was more modest. Molecular modeling of integrin binding indicated that Hyl glycosylation directly impacted the association between the α3β1 integrin metal ion‐dependent adhesion site (MIDAS) and the receptor binding site within type IV collagen. The Fmoc solid‐phase strategy ultimately allowed for chemical biology approaches to be utilized to study tumor cell interactions with glycosylated collagen sequences and document the modulation of receptor interactions by Hyl post‐translational modification. Abstract :